1995
DOI: 10.1111/j.1502-3931.1995.tb01611.x
|View full text |Cite
|
Sign up to set email alerts
|

Elliptic Fourier shape analysis of fossil bivalves: some practical considerations

Abstract: Elliptic Fourier shape analysis is a powerful, though under‐utilized, biometric tool that is particularly suited for the description of fossils lacking many homologous landmarks, such as several common bivalve groups. The method is conceptually more parsimonious than more traditional biometric methods based on discrete linear and angular measurements. Most importantly, however, shape analysis captures a much higher proportion of the morphological information resident in any fossil than analyses based on discre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
259
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(265 citation statements)
references
References 14 publications
(22 reference statements)
1
259
0
5
Order By: Relevance
“…The coefficients of the first harmonic, describing the best-fitting ellipse to the original outline, were used to standardize the size, orientation, and starting point of the molar outlines. These coefficients correspond to residuals after standardization and should not be included in following statistical analyses (37).…”
Section: Methodsmentioning
confidence: 99%
“…The coefficients of the first harmonic, describing the best-fitting ellipse to the original outline, were used to standardize the size, orientation, and starting point of the molar outlines. These coefficients correspond to residuals after standardization and should not be included in following statistical analyses (37).…”
Section: Methodsmentioning
confidence: 99%
“…Elliptical Fourier harmonics were extracted from smoothed otolith outlines (using 200 smoothing iterations) using the momocs package in R (http://cran.r-project.org/web/packages/Momocs/ Momocs.pdf, accessed 12 August 2015. The Fourier power equation (Crampton 1995) showed that over 99.9% of the variability in shape was captured by the first 12 harmonics. Each harmonic is composed of four coefficients (a n , b n , c n and d n ).…”
Section: Image Capture and Extraction Of Shape Variablesmentioning
confidence: 99%
“…The first ellipse (defined by the coefficients A 1 , B 1 , C 1 , and D 1 ) contains information about the size, position and rotation of the molar, and has been used to standardize the outline data. Hence, the first three coefficients were not retained for the statistical analysis, as they correspond to residuals after standardization (Crampton 1995;Renaud et al 1996). The fourth one, D 1 , corresponding to the minor axis of the ellipse, contains information about the elongation of the molar and was conserved in the analysis .…”
Section: Outline Analysesmentioning
confidence: 99%